2012
DOI: 10.1108/09578231211264694
|View full text |Cite
|
Sign up to set email alerts
|

Administrator career paths and decision processes

Abstract: PurposeThe purpose of this paper is to present qualitative evidence on the processes and forces that shape school administrator career paths.Design/methodology/approachAn embedded case study approach is used to understand more than 100 administrator career transitions within the Delaware education system. Semi‐structured interview data were collected from 48 principals and assistant principals. Coding and analysis occurred through an iterative process, revealing patterns in processes and forces influencing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 30 publications
1
58
0
1
Order By: Relevance
“…For instance, Fraser and Brock (2006) applied narrative surveys and structured interviews on 47 random principals in elementary and secondary schools in New South Wales, and identified incentive factors (e.g., district support, professional development, support from teachers and parents, autonomy) and disincentive factors (e.g., stress from work, insufficient remuneration, staff issues, and demanding and disgruntled parents) that are related with principal retention. In addition, Farley-Ripple, Raffel, et al (2012) applied a case study with more than 100 administrators’ career transitions in Delaware, and found that economic benefits, working relations with multiple stakeholders, and the availability of opportunities into the district central office were all critical factors for principal retention. More recently, Fuller et al (2015) analyzed survey data from a sample of principals in Texas and found that intrinsic rewards, overall workload, and a feeling of effectiveness were important factors influencing principal retention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Fraser and Brock (2006) applied narrative surveys and structured interviews on 47 random principals in elementary and secondary schools in New South Wales, and identified incentive factors (e.g., district support, professional development, support from teachers and parents, autonomy) and disincentive factors (e.g., stress from work, insufficient remuneration, staff issues, and demanding and disgruntled parents) that are related with principal retention. In addition, Farley-Ripple, Raffel, et al (2012) applied a case study with more than 100 administrators’ career transitions in Delaware, and found that economic benefits, working relations with multiple stakeholders, and the availability of opportunities into the district central office were all critical factors for principal retention. More recently, Fuller et al (2015) analyzed survey data from a sample of principals in Texas and found that intrinsic rewards, overall workload, and a feeling of effectiveness were important factors influencing principal retention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Policy makers especially at the district level have the power and responsibilities to improve school performance by hiring effective principals and meanwhile providing beneficial working conditions for them. Furthermore, given the expanding roles and challenges nowadays principals assume in school leadership and management, many working conditions such as salary and job benefits, workload, school disciplinary environment, and principal influences in school are becoming important concerns for many principals when considering the entry, mobility, and exit of the principalship (e.g., Farley-Ripple, Raffel, & Christine Welch, 2012; Fuller, Hollingworth, & Young, 2015; Loeb et al, 2010; Pijanowski, Hewitt, & Brady, 2009; Tekleselassie & Villarreal, 2011). Therefore, it is critical to for policy makers to understand how working conditions can influence principal turnover in order to retain principals for long-term school development and student success.…”
Section: Introductionmentioning
confidence: 99%
“…More important, district central offices can be key providers of supports for helping principals develop capacity for instructional leadership (Honig, 2012(Honig, , 2014. In that sense, strong district support enhances principals' efficacy, because it creates conditions and provides supports for principals' instructional leadership strategies and practice (Farley-Ripple et al, 2012;Leithwood & Jantzi, 2008). However, little empirical research has examined how district influence affects principals' decision-making discretion in schools.…”
Section: Other Stakeholders' Influence In School Decision Makingmentioning
confidence: 99%
“…While a growing set of literature has begun to consider the pipeline of experiences and training that lead to the principalship (DeAngelis and O'Connor, 2012;Farley-Ripple et al, 2012;Fuller et al, 2011;Myung et al, 2011), little research has explored the context effects of having been a teacher in the school that the principal then leads. For urban school leadership, context matters (Bryk et al, 2010;Cuban, 2001;Klar and Brewer in press), and our findings for Chicago reinforce this notion.…”
mentioning
confidence: 99%